2021
DOI: 10.1038/s41388-021-02005-y
|View full text |Cite
|
Sign up to set email alerts
|

Intron retention-induced neoantigen load correlates with unfavorable prognosis in multiple myeloma

Abstract: Neoantigen peptides arising from genetic alterations may serve as targets for personalized cancer vaccines and as positive predictors of response to immune checkpoint therapy. Mutations in genes regulating RNA splicing are common in hematological malignancies leading to dysregulated splicing and intron retention (IR). In this study, we investigated IR as a potential source of tumor neoantigens in multiple myeloma (MM) patients and the relationship of IR-induced neoantigens (IR-neoAg) with clinical outcomes. MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…Type 1 diabetes is an evolving field of interest where splicing alterations can unveil novel immunogenic epitopes (Wu et al, 2021). In addition, IR is a frequent event in many cancer types, and our recent studies have shown that IR-induced neoantigens may be a useful biomarker for predicting survival in multiple myeloma and pancreatic cancer patients (Dong et al, 2021(Dong et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Type 1 diabetes is an evolving field of interest where splicing alterations can unveil novel immunogenic epitopes (Wu et al, 2021). In addition, IR is a frequent event in many cancer types, and our recent studies have shown that IR-induced neoantigens may be a useful biomarker for predicting survival in multiple myeloma and pancreatic cancer patients (Dong et al, 2021(Dong et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, recurrent stop codon mutations leading to readthrough into 3’ UTRs have been detected in over 400 cancer-related genes (Dhamija et al, 2020). Further supporting elevated noncanonical ORF translation in cancer, peptides derived from noncoding regions account for the majority of tumor-specific antigens (Laumont et al, 2018; Smart et al, 2018; Xiang et al, 2021), and tend to be associated with unfavorable prognoses for patients (Dong et al, 2021). Similarly, increased intron retention and other aberrant splicing events are associated with aging and neurodegeneration (Adusumalli et al, 2019; Hsieh et al, 2019; Mariotti et al, 2022; Mazin et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…While an improvement, our intron persistence metric only partially accounts for admixed splicing patterns from different cell types in a mixed-cell sample such as HX1. Like other RI detection studies [1517, 25, 31, 34, 43], our approach is explicitly linked to annotation (here, GENCODE v35) and therefore reports IR only relative to annotated transcripts, ignoring potential unannotated transcripts. We also did not explore the entanglement of biological and technical effects in the length of persistent introns: shorter introns are more likely to be retained [43, 55, 56], but the length limit of PacBio Iso-Seq reads of up to 10 kilobases means that any molecules with longer persistent introns were not considered in this study.…”
Section: Discussionmentioning
confidence: 99%